EFFECT OF DRUG ABUSE ON THE YOUTH LIVELIHOODS IN NORTHERN DIVISION, MBALE CITY - AKELLO JANET JESCAH (My University, 2024)
ABSTRACT Drug abuse among the youth is one of the wide spread problem of modern time with substances consumed clandestinely forcing youth to neglect their livelihoods. Even no attention by both policy and academia has been given to the unlimited effort by youth to stop drug abuse and effectively participate in livelihood productivity. This study was aimed at determining the effect of drug abuse on youth livelihoods. The purpose of the study was to assess the effects of drug abuse on youth’s livelihoods in Eastern division in Mbale city. The study was guided by three specific objectives namely: To examine the physical health implications of drugs on the youth’s livelihoods in Eastern Division of Mbale City, to investigate the mental health effects associated with drugs on the youths livelihoods in Eastern Division of Mbale City and to analyze the health risks resulting from drugs to the youths in Eastern Division of Mbale city. Data was collected from 80 respondents in Eastern Division of Mbale City who included opinion leaders, child welfare officers and parents. Data was collected using surveys and interviews. Study participants were identified using probability and non-probability sampling. The study employed a mixed research approach using descriptive study and case study designs and data processing was done through editing of the data which will be coded for further data analysis. Data from questionnaires was analyzed using both descriptive statistics while interview data was analyzed using frequency analysis by counting the number of times of responses had by the respondents. Findings showed that drug abuse results into livelihood neglect by youth and eating and sleeping disorders. Drug abuse leads to psychological distress among youth and also drug abuse creates grief among family members particularly youths. Creates physical body weakness of youths. Other findings show that drug abuse affect reasoning and decision making and this lowers youth involvement in livelihoods and cognitive problems reduces effective participation in youth livelihoods. Drug abuse leads to mental problems which reduce involvement in youth livelihoods it may lead to leads to youth suicide which results into failure of livelihoods. Drug abuse leads to alcohol and other drug use which lowers youth involvement in livelihoods. Further, the study found that Results into emotional anger among youth negatively affect their livelihoods and drug abuse creates worry among youth and tis lower their involvement in youth livelihood. Drug abuse results into emotional stress among youth and this affects their livelihoods and also creates fear and emotional distress among youth and this slows livelihood productivity. The study recommended strengthening the capacity of local council in fighting drug and substance abuse, increasing funding of these programmes in lower administrative units and also mobilizing communities and stakeholders to step forward in support youth livelihoods.